A SCUBA-2 850 μm survey of heavily reddened quasars at z ∼ 2. Issue 4 (28th January 2020) - Wethers, Clare F; Banerji, Manda; Hewett, Paul C; Jones, Gareth C
ABSTRACT: We present new 850 μ m SCUBA-2 observations for a sample of 19 heavily reddened Type-I quasars at redshifts z ∼ 2 with dust extinctions of A V ≃ 2–6 mag. Three of the 19 quasars are detected at >3σ significance corresponding to an 850 μ m flux-limit of ≳4.8 mJy. Assuming the 850 μ m flux is dominated by dust heating due to star formation, very high star formation rates (SFR) of ∼2500–4500 M⊙ yr −1 in the quasar host galaxies are inferred. Even when considering a large contribution to the 850 μ m flux from dust heated by the quasar itself, significant SFRs of ∼600–1500 M⊙ yr −1 are nevertheless inferred for two of the three detected quasars. We stack the remaining 16 heavily reddened quasars and derive an average 3σ upper limit on the SFRs in these quasar host galaxies of <880 M⊙ yr −1 . The number counts of sub-mm galaxies in the total survey area (134.3 arcmin 2 ) are consistent with predictions from blank-field surveys. There are, however, individual quasars where we find evidence for an excess of associated sub-mm galaxies. For two quasars, higher spatial resolution and spectroscopic ALMA observations confirm the presence of an excess of sub-mm sources. We compare the 850 μ m detection rate of our quasars to both unobscured, ultraviolet luminous quasars as well as the much more obscured population of mid-infrared luminous Hot Dust Obscured Galaxies (HotDOGs). When matched by luminosity and redshift, we find no significant differences in the 850 μ m flux densities of these various quasar populations given the current small sample sizes.